On the Verge Between Language and Translation - Walczynski, Marcin; Walczynski, Marcin (Peter Lang, 2019)
This book explores a range of topics situated in the overlapping areas of theoretical linguistics, applied linguistics and translation studies. The first part of the book comprises five original contributions on topics ranging from general linguistics to applied linguistics while the second part comprises eleven original contributions exploring selected aspects of theoretical, descriptive and applied translation studies. This book also initiates the publishing activity of the Department of Translation Studies, established at the Institute of English Studies, University of Wroc?aw, Poland.